From Cognition to the Imaginal: Fostering Self-Understanding from and through Emotions in Adult Learning - John Dirkx; Ben Espinoza (Adult Education Research Conference, 2017)
Based on a critical review of the literature, this paper explores the imaginative contribution emotions make to self-understanding and how it compliments the view of emotion as a form of cognition in adult learning.
Keywords: emotion in adult learning; self-understanding; transformative learning